Penegakan Hukum terhadap Tindak Pidana Pemblokiran Jalan: Studi Kasus Polres Bima - Jainudin Jainudin; Erham Erham; Aman Maarij (CV Rewang Rencang, 2025)
This study aims to analyze law enforcement against the criminal act of road blockades carried out during demonstrations, particularly in the jurisdiction of the Bima Police, West Nusa Tenggara. In a democratic country, demonstrations are a fundamental right guaranteed by law, but their implementation must remain within legal boundaries to avoid disrupting public order. This research employs an empirical legal method with statutory and sociological approaches. Data were obtained through interviews and field observations, as well as literature studies on relevant laws and legal references. The findings indicate that road blockades conducted illegally—such as placing stones, wood, or burning tires on public roads—constitute criminal offenses. These actions violate provisions under Article 192 of the Indonesian Penal Code (KUHP), Article 63 of Law No. 38 of 2004 on Roads, and Article 274 of Law No. 22 of 2009 on Road Traffic and Transportation. In addition, violators may also be subject to sanctions under Law No. 9 of 1998 and Police Regulation No. 7 of 2012. In the Bima Police case, law enforcement authorities applied persuasive and, when necessary, limited repressive measures in accordance with legal procedures to resolve traffic obstruction caused by demonstrations. The study highlights the importance of balancing democratic freedoms with firm law enforcement to safeguard public interest and order.